Songs in the genus Uromenus (Orthoptera: Tettigoniidae: Ephippigerini): A review with new information about some species - Heller, Klaus-Gerhard; Puskás, Gellért; Szövényi, Gergely; Chobanov, Dragan P. (Zootaxa, 2021)
With nearly 60 described forms Uromenus is the most species-rich genus of the tribe Ephippigerini, a west Palearctic group of flightless bush-crickets (katydids). As it is typical for bush-crickets, Uromenus males produce species-specific calling songs to attract females prepared to mate. These insects are relatively large and their songs have always components audible to humans. Nevertheless, acoustical information are available only for few species. Also the phylogenetic relationships of species and species groups are poorly known. In this paper we present new data on the song and morphology of several species (U. dyrrhachiacus, U. elegans, U. finoti, U. galvagnii, U. robustus, U. tobboganensis and U. innocentii) and give a review of all published acoustical data. Judging from the still few data, as in other Ephippigerini the song patterns often seem to contain species-group characteristics making them candidates to be used in phylogenetic studies. Additionally, we have studied the female stridulatory organs which are unique in structure in Ephippigerini and completely different from those of the males. Despite in Uromenus used only for defensive stridulation, possibly species-specific similarities in structure between males and females exist.